The chariot at dusk - Teerdhala, Swati (Teerdhala, Swati. Tiger at midnight trilogy, 2021)
"The Yavar are attacking from every front, tracking down Kunal and Reha in the remote mountains, kidnapping Harun, in search of legendary artifacts that will give them the power to break the precarious janma bond and release the destructive magic back into the lands. Now that the race is on to find the missing artifacts, Esha must put aside her rage and work with Kunal again, but can she find the strength to forgive him, or will the Viper have her revenge at any cost?"--